2016 IEEE-RAS 16th International Conference on Humanoid Robots (Humanoids) 2016
DOI: 10.1109/humanoids.2016.7803321
|View full text |Cite
|
Sign up to set email alerts
|

Exercising with a humanoid companion is more effective than exercising alone

Abstract: Abstract-Engineers developing socially assistive robots for promoting a healthy and active lifestyle are facing several mechanical and interactive design challenges. In this paper we are answering the question whether a humanoid robot exercising partner capable of working out together with its user makes significant improvement in the user's engagement. We conducted a study with 56 participants doing five isometric exercises in three conditions comparing the differences between working out alone (IC), with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Users' perceptions of their interaction with the robot thus improved, relative to their initial expectations. Schneider and Kümmert [66] also investigate the differences in motivation created by a robot that solely instructs users (instructor role) and one that exercises alongside the user (companion role); people appear more motivated by the robot companion role. Finally, in a robot coaching scenario [33], an elderly user study cites engagement and enjoyment while exercising but also reveals some difficulties, such as hearing instructions, focusing on the physical aspects of the robot while ignoring verbal instructions, and confusion associated with performing sequences of gestures.…”
Section: Robotic Coachesmentioning
confidence: 99%
“…Users' perceptions of their interaction with the robot thus improved, relative to their initial expectations. Schneider and Kümmert [66] also investigate the differences in motivation created by a robot that solely instructs users (instructor role) and one that exercises alongside the user (companion role); people appear more motivated by the robot companion role. Finally, in a robot coaching scenario [33], an elderly user study cites engagement and enjoyment while exercising but also reveals some difficulties, such as hearing instructions, focusing on the physical aspects of the robot while ignoring verbal instructions, and confusion associated with performing sequences of gestures.…”
Section: Robotic Coachesmentioning
confidence: 99%
“…We therefore hypothesized that if participants believed that their partner were an humanoid robot such as the iCub, the perception of the partner's apparently effortful contribution could elicit a sense of commitment to the interaction. This hypothesis is also supported by research showing that participants were more motivated while performing an exercising task with an embodied robot partner than with a virtual partner (Fasola & Matarić, 2013), and by research indicating that participants were more motivated when exercising jointly with a robot partner than when exercising individually according to the instructions of a robot teacher (Schneider & Kümmert, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…While several studies showed the potential of virtual agents [10,11] and physical robots [12] to enhance engagement and learning in health, physical activity or social contexts, Fasola et al [13] showed better assessment by the elderly subjects of the physical robot coach compared to virtual systems. Robots for coaching physical exercises have been recently presented [14,15,16]. These approaches employed robots with few degrees of freedom that facilitates the imitation process.…”
Section: Related Workmentioning
confidence: 99%